TEM Guidelines on Work Zone Safety - United Nations Economic Commission for Europe (United Nations, 2022)
This publication is an overview of the current state of practice across Trans-European North-South Motorway (TEM) member countries revealed a multitude of design and signing practices for road work zones, with different characteristics that are often hard to understand for the road users, especially in cross-border traffic. The Guidelines are based on a comprehensive review of the most relevant road work zones guidelines, standards, studies, and projects and address current trends, standards, technologies, and equipment in road work zones on motorways in TEM Member Countries. A meta-analysis of the current situation and existing national guidelines and standards for road work zones was carried out to identify good practice solutions and to develop a unified range of road work zone safety principles and measures that should govern the planning, design, implementation, and operation of road work zones in TEM member countries to mitigate their negative safety effects on workers and road users. Finally, main challenges were identified and recommendations for TEM member countries to further improve work zone safety were given.